1994
DOI: 10.4037/ajcc1994.3.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of position on selected hemodynamic parameters in postoperative cardiac surgery patients

Abstract: BACKGROUND: Indirect/noninvasive blood pressure, heart rate and central venous pressure are frequently monitored hemodynamic parameters in postoperative cardiac surgery patients. No previous studies have explored the effect of lateral position on these variables in this population. OBJECTIVES: To determine differences in (1) blood pressure, central venous pressure, or heart rate measurements among postoperative cardiac surgery patients due to position (supine, 45 degrees right lateral, and 45 degrees left late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For reasons of simplification, venous pressure was neglected in the FFR calculation in the course [1, 25]. It is known that changing from the supine position to the prone position results in significant differences in central venous pressure [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…For reasons of simplification, venous pressure was neglected in the FFR calculation in the course [1, 25]. It is known that changing from the supine position to the prone position results in significant differences in central venous pressure [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Tor et al (2019) [16] did not detect any difference in systolic blood pressure values in the measurements they made in the supine and semi fawler positions in intensive care patients. Emerson and Banasik (1994) [5] emphasized in their study that different positions cause significant changes in systolic and diastolic blood pressure. Thijsen et al (2019) [13] found PI < 1 at a rate of 52.8% in their study on intensive care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalence was predefined based on the normal ranges. For heart rate, a change of more than ± 5 beats per minute (Emerson & Banasik ), for breathing a change of more than ± 3 breaths per minute (Smith et al . ) and for blood pressure a change of ± 5 mmHg are considered to be relevant (Aries et al .…”
Section: Methodsmentioning
confidence: 99%